Determination of Phosphodiesterase Type-5 Inhibitors (PDE-5) in Dietary Supplements - Oana Ramona Cătălina Gheorghiu; Anne Marie Ciobanu; Claudia Maria Guțu; Carmen Lidia Chițescu; Giorgiana Valentina Costea; Daniela Mădălina Anghel; Ana Maria Vlasceanu; Daniela Luiza Baconi (Molecules, 2023)
This study proposed a high-performance thin-layer chromatography (HPTLC) screening method to detect phosphodiesterase 5 (PDE-5) inhibitors as possible adulterant agents in various dietary supplements. Chromatographic analysis was performed on silica gel 60F254 plates using a mixture of ethyl acetate:toluene:methanol:ammonia in a volume ratio of 50:30:20:0.5 as a mobile phase. The system provided compact spots and symmetrical peaks of sildenafil and tadalafil with retardation factor values of 0.55 and 0.90, respectively. The analysis of products purchased from the internet or specialized stores demonstrated the presence of sildenafil, tadalafil, or both compounds in 73.3% of products, highlighting inadequacies and inconsistencies in the labeling, as all dietary supplements were declared to be natural. The results were confirmed using ultra-high-performance liquid chromatography coupled with a positive electrospray ionization high-resolution tandem mass spectrometry (UHPLC-HRMS-MS) method. Furthermore, in some samples, vardenafil and various analogs of PDE-5 inhibitors were detected using a non-target HRMS-MS approach. The results of the quantitative analysis revealed similar findings between the two methods, with adulterant quantities found to be similar to or higher than those in approved medicinal products. This study demonstrated that the HPTLC method is a suitable and economical method for screening PDE-5 inhibitors as adulterants in dietary supplements intended for sexual activity enhancement.